UTILIZATION OF GAMASIS (ISLAMIC CHILDREN'S GAMES) WITH WORDWALL WEBSITE AS LEARNING MEDIA IMPLEMENT LEADERSHIP OMAR BIN KHATTAB IN CLASS 6 SD - Fadhila Tunissa, Izmi; Salamah, Siti; Wiramanggala, Ayu Nabila; Aprilianti, Alda Dwi; Aeni, Ani Nur (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
In this era modern education, learning media cannot be separated from the on going learning media cannot be separated from the ongoing learning process in elementary schools. This study aims to improve political education in the Islamic perspective on Umar bin Khattab’s leadership using the Islamic Childern’s Game (GAMASIS) in class VI SDN Narawita 02. The focus of this research is to improve the leardership spirit of students in SD according to Umar bin Khattab’s leadership. This research is a qualitative research with D&D method and ADDIE model. The subjects of this study were students of Class VI SDN Narawita 02 which opened 27 people. Indicators of success in research can be measured by obtaining a score of answers in the answers to Umar bin Khattab’s leadership questions on the Wordwall site. The results showed that 98% of the quality of learning media very good criteria was stated to be relevant to the results of research and validation of Islamic religious education (PAI) teachers at SDN Narawita 02, as well as Islamic Chilldern’s Games learning media (GAMASIS) which were suitable for use and did not need to be revised.